1998
DOI: 10.1021/jf970561i
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of Emamectin Benzoate in Aqueous Solutions

Abstract: The half-life of [14C]4‘‘-deoxy-4‘‘-(epi-methylamino)avermectin B1a (MAB1a) benzoate (1 ppm) photodegradation in buffer (pH 7), natural pond water, and sensitized buffer (1% acetone in pH 7 buffer) determined at Three Bridges, NJ (latitude ∼40° N) during the fall season under natural sunlight was 22, 7, and 1 days, respectively. The half-life of [14C]MAB1a benzoate (10−12 ppm) photodegradation in buffer (pH 7) containing 1% (v/v) acetonitrile, ethanol, or acetone as cosolvent under continuous exposure with a x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…In the material test with azamethiphos, glass bottles demonstrated the second lowest concentration after 24 h. However, in the depletion studies of azamethiphos in glass bottles, high concentrations (>90% of nominal concentration) were detected after 24 h. Depletion of EMB might have been caused by photodegradation and not adsorption to material as shown in the study by Mushtaq et al . (). The test bottles in the present study were, however, only exposed to light during sampling.…”
Section: Mean (±Sem) Concentration Of Chemicals Left In 1 L Of Sea Wamentioning
confidence: 97%
“…In the material test with azamethiphos, glass bottles demonstrated the second lowest concentration after 24 h. However, in the depletion studies of azamethiphos in glass bottles, high concentrations (>90% of nominal concentration) were detected after 24 h. Depletion of EMB might have been caused by photodegradation and not adsorption to material as shown in the study by Mushtaq et al . (). The test bottles in the present study were, however, only exposed to light during sampling.…”
Section: Mean (±Sem) Concentration Of Chemicals Left In 1 L Of Sea Wamentioning
confidence: 97%
“…The involvement of pressing wavelengths below 290 nm with transmission hydroxyl radicals was discarded on the basis of the lack of filters. The observed half-life times varied from 10 to 40 influence of isopropanol. The authors suggest the phenol min in the presence of TiO , one or two orders of may react with positive holes in goethite, the electron 2 magnitude lower than in its absence.…”
Section: Factors Tion Of Methyl Parathion Hoo-dimethyl O-4-nitrophenylmentioning
confidence: 99%
“…Mushtaq et al [40] studied the photodegradation of emamectin benzoate h40-deoxy-40-(epi-methylamino)avermectin B benzoatej in aqueous solution buffered to pH 7 1a and natural pond water under sunlight. Avermectins are 16-member lactones, used as insecticides.…”
Section: 4-bis[bis(isopropoxycarbonyl)methylene]-13-dithietanementioning
confidence: 99%
See 1 more Smart Citation
“…In crop protection, the parent drug, generally, is the major residue that occurs after application of MLs to crops. On exposure to light, it has been shown that these molecules can isomerise to form an 8,9-Z-isomer [79][80][81][82]. On derivatisation, abamectin and it's 8,9-Z-isomer were converted into the same fluorescent derivative [83].…”
Section: Monitoring For Macrocyclic Lactone Residues In Foodmentioning
confidence: 99%